Customer care : a training manual for library staff - Gannon-Leary, Pat.; McCarthy, Michael D. (Oxford, UK : Chandos Pub., 2010)
Annotation The book provides a detailed customer care course suitable for delivery to library staff at all levels. It can be used as a stand-alone, reference work for customer care processes and procedures or, alternatively, it can be used by library staff to tailor a customer care course to suit the requirements and training needs of their own staff. As it relies heavily on facilitation techniques, the training may not necessarily be delivered by staff responsible for staff training and development but can be delivered by a cross-departmental team of facilitators. This empowers these staff and gives them both skills and development opportunities.
Preparation -- The introduction -- What is customer service? -- Who are our customers? : the customer service chain -- Communication -- Questioning and active listening -- Handling complaints -- Dealing with challenging situations -- Life positions and the OK Corral : being more confident and assertive -- Suggestions for improvement -- Teambuilding -- What are we good at, and what is our future? : action planning -- Wrapping it up -- Conclusion.
Includes bibliographical references and index.
Keywords: Public services (Libraries); Libraries -- Customer services; Library employees -- In-service training